Fabrication and characterization of chitosan, polyvinylpyrrolidone, and cellulose nanowhiskers nanocomposite films for wound healing drug delivery application. Issue 9 (22nd May 2017) - Hasan, Abshar; Waibhaw, Gyan; Tiwari, Sakshi; Dharmalingam, K.; Shukla, I.; Pandey, Lalit M.
Abstract: This study describes the preparation of composite film using chitosan (CS) and polyvinylpyrrolidone (PVP) with incorporated cellulose nanowhiskers (CNWs) for drug delivery application. CNWs were prepared by acid hydrolysis of cellulose with sulfuric acid. Field emission scanning electron microscopy studies revealed nanofibrous morphology of CNWs with 20–30 nm diameter and 200–250 nm in length. X‐ray powder diffraction analysis confirmed highly crystalline nature of CNWs with 92.81% crystallinity. Incorporation of CNWs enhanced the thermal and mechanical properties of films. Fourier transform infrared spectroscopy data showed physical interactions between polymer‐polymer and polymer‐drug. Films prepared with CNWs showed improved swelling behavior which resulted in sustained drug release from polymeric matrix. In vitro curcumin release data were fitted with two‐step release model; Step 1 as desorption from the outer surface of the film, and Step 2 as diffusion from within the film and subsequent desorption. The release kinetics confirmed biphasic release profile with different release rates along with diffusion controlled curcumin release. Prepared films showed high biocompatibility with excellent antibacterial activities. Overall, the performed studies confirmed CS–PVP–CNWs based release system can as a potential candidate for wound dressing applications with sustained drug release. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2391–2404, 2017.